The Gravity Model of Trade: The Case of Central and Eastern Europe - Nazarii Lypko (LeXonomica, 2022)
The main patterns of international trade in the countries of Central and Eastern Europe have been analysed in the paper. The gravity model, estimated for a large sample of bilateral trade flows for the analysed states, has been used as a benchmark. The model has been updated according to the modern conditions in the international economy. The emphasis has been made on the analysis of products' trade since the trade of services requires separate modelling. The purpose of the paper was to find the main factors that determine gravity trends in international trade in Central and Eastern Europe. It has been proven that the distance between countries and their gross domestic products are still crucial factors which determine trade flows between them. Additionally, the influence of the product structure of export has been considered. A higher share of value-added export increases bilateral trade between the countries. Common past for the analysed countries boosts trade between them because of the presence of historical trade traditions and the development of regional production agglomeration. It has been proven that the gravity equation remains a simple and reliable model of the factors which determine the trade between countries.Povzetek. V prispevku so analizirani glavni vzorci mednarodne trgovine v državah srednje in vzhodne Evrope. Kot merilo je bil uporabljen gravitacijski model, ocenjen za velik vzorec dvostranskih trgovinskih tokov analiziranih držav. Model je bil posodobljen glede na sodobne razmere v mednarodnem gospodarstvu. Poudarek je bil na analizi trgovine z izdelki, saj trgovina s storitvami zahteva ločeno modeliranje. Namen prispevka je bil ugotoviti glavne dejavnike, ki določajo gravitacijska gibanja v mednarodni trgovini v Srednji in Vzhodni Evropi. Izkazalo se je, da sta razdalja med državami in njihov bruto domači proizvod še vedno ključna dejavnika, ki določata trgovinske tokove med njimi. Poleg tega je bil upoštevan tudi vpliv strukture izdelkov pri izvozu. Večji delež izvoza z dodano vrednostjo povečuje dvostransko trgovino med državami. Skupna preteklost analiziranih držav spodbuja trgovino med njimi zaradi prisotnosti zgodovinskih trgovinskih tradicij in razvoja regionalnih proizvodnih aglomeracij. Dokazano je bilo, da gravitacijska enačba ostaja preprost in zanesljiv model dejavnikov, ki določajo trgovino med državami.